MANAJEMEN PEMBINAAN KEDISIPLINAN SANTRI DALAM MENGIKUTI KEGIATAN KEAGAMAAN DI PONDOK PESANTREN NURUS SHIBYAN AMBAT TLANAKAN PAMEKASAN - Rofiatun Rofiatun; Mohammad Thoha (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2019)
Discipline is defined as an important exercise and character with the intention that all actions always obey the order, obedience, and rules of the order. This research uses a qualitative approach and the type is descriptive. The results of the study show that: (1) Management of disciplining students in participating in religious activities in the Islamic Boarding School of Nurus Shibyan Ambat Tlanakan Pamekasan is effective in accordance with applicable rules and regulations while fostering religious discipline activities for all students must participate in religious ritual activities, prayer in congregation, book deliberations, and from every student has a companion cleric, and regulated by the pesantren curriculum, (2) Supporting and inhibiting factors in fostering student discipline in participating in religious activities at Nurus Shibyan Islamic Boarding School Ambat Tlanakan Pamekasan, are supporting factors related to the potential of students, teacher / religious teacher readiness to keep fighting, and religious enthusiasm to fight by Allah while the inhibiting factors are some naughty students, laziness of children to participate in activities in the cottage, facilities which are partially inadequate, and lack of funds.